Occupations at risk: The task content and job security - Ljubica Nedelkoska (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
While earlier literature proposed a monotonic relationship between the skill level (as measured by educational attainment) and employment prospects, recent literature suggests that this relationship has changed and that it is now necessary to distinguish between different kinds of skills and tasks in order to understand the recent occupational structure changes in developed economies. We study the occupational dynamics in the western part of Germany over the last three decades and confirm that occupations characterized by high intensity of interactive and problem-solving tasks have been increasing their employment share at the expense of occupations with a high level of codifiable tasks (tasks that can be described by step-by-step procedures or rules). We provide evidence at the individual level that jobs which involve a high instance of codifiable tasks are associated with lower job security. The pattern is present at different educational levels and in various broadly defined industries. It is also present in both the pre-reunification period and the period after the German reunifiation. The results are in line with a theory of technological change where computer-based technologies substitute for codifiable tasks (Autor, Levy, and Murnane, 2003).
Keywords: J21; J24; J63; 330; skills; tasks; occupations; job security; Automation; Arbeitsschutz; Qualifikation; Arbeitsorganisation